Australasian emergency ultrasound: A survey on the current status. (30th November 2021) - Manivel, Vijay; Kennedy‐Smith, Elissa; Mirmiran, Behzad; Cormack, Carolynne J; Garner, Alan; Condous, George
Abstract: Objective: Emergency ultrasound (EUS) has become an integral part of emergency medicine, and the core pillars of governance, infrastructure, administration, education and quality assurance (QA) are vital for its quality and continued growth. We aimed to assess the status of these vital pillars among Australasian EDs. Methods: A survey among the clinical leads in ultrasound (CLUS) in Australasian EDs from November 2020 to April 2021. Results: We analysed a total of 98 responses from CLUS representing 98 EDs. Most CLUS (85%) held EUS qualifications (CCPU 57%, DDU 18%, other 9%) but 15% had none. Only 66% of CLUS had dedicated clinical support time, and a mere 5% had administrative personnel support. Up to three ultrasound machines in 62% of EDs, but only 26% of EDs had secured image archiving facilities. In‐house credentialing and the Australasian College for Emergency Medicine (ACEM) trainee special skills placement were available in 50% and 32% of EDs, respectively. Only 11% of EDs had regular EUS training for FACEMs, and only 66% of EDs had regular EUS education for emergency medicine trainees. Only 20 EDs had sonographer educators. Regarding EUS QA, only 33% of EDs provided formal EUS report, 23% of EDs conducted regular image reviews and 37% of EDs audited EUS performance. Only 35% of EDs had high‐level disinfection equipment, and 56% of EDs had formal transducer disinfection protocols. Conclusion: Despite ACEM recommendations for the practice of EUS, Australasian EDs still lack vital governance, administrative support, infrastructure, education and QA processes. Prompt actions such as ACEM mandating these recommendations are required to improve resource allocation by health services. Abstract : Emergency ultrasound in Australasian EDs lacks vital governance, administrative support, infrastructure, education and quality assurance processes. ACEM's recommendations for EUS are not adhered to by many health services, and mandating these recommendations is an essential step in the right direction.